2009
DOI: 10.1073/pnas.0912533106
|View full text |Cite
|
Sign up to set email alerts
|

PGC-1α negatively regulates hepatic FGF21 expression by modulating the heme/Rev-Erbα axis

Abstract: FGF21 is a hormone produced in liver and fat that dramatically improves peripheral insulin sensitivity and lipid metabolism. We show here that obese mice with genetically reduced levels of a key hepatic transcriptional coactivator, PGC-1␣, have improved wholebody insulin sensitivity with increased levels of hepatic and circulating FGF21. Gain-and loss-of-function studies in primary mouse hepatocytes show that hepatic FGF21 levels are regulated by the expression of PGC-1␣. Importantly, PGC-1␣-mediated reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
99
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(107 citation statements)
references
References 50 publications
6
99
0
Order By: Relevance
“…Chronic reduction of hepatic PGC-1α expression in mice increased FGF21 expression (27). In this scenario, the metabolic status of the animal resembles that of starvation, when PGC-1α levels are low and FGF21 functions to mediate ketogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic reduction of hepatic PGC-1α expression in mice increased FGF21 expression (27). In this scenario, the metabolic status of the animal resembles that of starvation, when PGC-1α levels are low and FGF21 functions to mediate ketogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Rev-erb␣ has been shown to modulate FGF21 expression in liver (62). Given the circadian expression of Rev-erb␣ in WAT, we hypothesized that the repression by Rev-erb␣ would also be rhythmic.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that FGF21 mRNA expression and circulating concentrations increased only after long-term fasting in mice (>16 h) when it is important for the regulation of adipose tissue catabolism and torpor, a state of decreased activity and metabolism (Estall et al, 2009). Similarly, Kliewer and Mangelsdorf (2010) indicated that FGF21 stimulates gluconeogenesis and ketogenesis in the context of prolonged fasting and starvation (>7 days fasting in humans) but not in the early stages of fasting.…”
Section: Hepatic Expression Of Somatotropic Axis Genesmentioning
confidence: 99%